2002
DOI: 10.1289/ehp.021101155
|View full text |Cite
|
Sign up to set email alerts
|

The origin, fate, and health effects of combustion by-products: a research framework.

Abstract: Incomplete combustion processes can emit organic pollutants, metals, and fine particles. Combustion by-products represent global human and environmental health challenges that are relevant not only in heavily industrialized nations, but also in developing nations where up to 90% of rural households rely on unprocessed biomass fuels for cooking, warmth, and light. These issues were addressed at the Seventh International Congress on Combustion By-Products, which convened 4-6 June 2001 in Research Triangle Park, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 53 publications
0
31
0
2
Order By: Relevance
“…(2) In a previous study of ours, performed in a JSR, we observed that the addition of DMM (CH 3 -O-CH 2 -O-CH 3 ) at ppm level resulted in a modification of the ratio of the concentrations of several PAH formed from the oxidation of indane [1]. Did you observe such a complex behavior in your experimental conditions?…”
Section: Commentsmentioning
confidence: 94%
See 1 more Smart Citation
“…(2) In a previous study of ours, performed in a JSR, we observed that the addition of DMM (CH 3 -O-CH 2 -O-CH 3 ) at ppm level resulted in a modification of the ratio of the concentrations of several PAH formed from the oxidation of indane [1]. Did you observe such a complex behavior in your experimental conditions?…”
Section: Commentsmentioning
confidence: 94%
“…A major objection to fossil fuel combustion is the emission of soot particles from diesel engines, gas turbines, industrial furnaces, and other devices [1]. One strategy for reducing these emissions is to add oxygen-containing hydrocarbons to the petroleum-derived fuels in current use.…”
Section: Introductionmentioning
confidence: 99%
“…M. Han et al: Different characteristics of char and soot in the atmosphere different measurements of thermochemical and optical techniques (Pöschl, 2005). EC has received more attention in recent years because it contributes to global warming, carries carcinogenic compounds, and causes serious health risks (Jacobson, 2001;Menon et al, 2002;Avakian et al, 2002;Hansen and Nazarenko, 2004;Koelmans et al, 2006). It is estimated that the contributions by EC to global warming, in terms of direct climate forcing, is second only to CO 2 (Jacobson, 2001), and reducing emissions of EC could mitigate the projected warming trends and delay the time of onset of the "dangerous" climate change (e.g.…”
mentioning
confidence: 99%
“…In large -scale epidemiological studies, susceptible populations were seen to be susceptible to increases in environmental particles (PM 10 ) of as little as 10 μ g/m 3 , suggesting that the toxicity of this PM 10 fraction was highly potent. Subsequent research focused on the primary, combustion -derived UF fraction as a likely major arbiter of these adverse effects (Avakian et al, 2002 ;Morawska and Zhang, 2002 ;Donaldson et al, 2005b ). The UF component of PM in urban air is dominated in numerical terms by the CDNPs, such as diesel soot, which have a number of components and properties that imbue them with toxic potency (Donaldson et al, 2003(Donaldson et al, , 2005b.…”
Section: Uf S In Particulate Matter ( Pm ) the Road To Concern Over mentioning
confidence: 99%